How Do Biotech Cluster Firms Catch Knowledge Spillovers? The Strong Impact Of The Institutional Mechanisms - Boufaden, Najoua (Journal of Applied Business Research, 2017)
This paper deals with the nature of the mechanisms supporting knowledge spillovers diffusion in high-tech clusters. The literature in the geography of innovation focuses on the existence of local knowledge spillovers, which are enhanced by geographic and technological proximity. However, the mechanisms explaining the diffusion of spillovers are not well understood. If knowledge spillovers exist, how does this knowledge diffuse among the actors? Do spillovers spread in the air, as suggested by Marshall? Or, are there mechanisms that explain their dissemination? Based on a firm survey data base and an original methodology, the paper explores the determinants of knowledge spillovers. The paper has twofold purposes; the first one is to determine the main mechanisms within a region enabling the diffusion of spillovers. The second objective is measuring the impact of these main mechanisms on firm’s innovation performance, indicating which of these mechanisms are more effective in transporting knowledge spillovers between agents. The results show new empirical evidences on the role played by institutions1 in the dissemination of externalities. However, informal mechanisms, such as face-to-face contacts commonly stressed in the literature, have no significant and negative effects in this case.